2022
DOI: 10.1136/jitc-2021-003939
|View full text |Cite
|
Sign up to set email alerts
|

FimH confers mannose-targeting ability to Bacillus Calmette-Guerin for improved immunotherapy in bladder cancer

Abstract: BackgroundBladder cancer is a common disease worldwide with most patients presenting with the non-muscle-invasive form (NMIBC) at initial diagnosis. Postoperational intravesical instillation of BCG is carried out for patients with high-risk disease to reduce tumor recurrence and progression to muscle invasive disease. However, BCG can also have side effects or be ineffective in some patients because it cannot enter the cancer cells. Thus, to improve the efficacy of BCG immunotherapy is the long-term pursuit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…A recent manuscript showed indirect evidence for this mechanism, demonstrating that BCG expressing the mannose-binding protein FimH had improved ability to adhere to urothelial cells and be internalized by them and also induced a more potent anti-tumor response as compared to wild type BCG. However, whether the improved efficacy of the FimH strain was through increased uptake by urothelial cells or via another mechanism was not shown [30].…”
Section: Interactions Between Bcg and Urothelial Cellsmentioning
confidence: 99%
“…A recent manuscript showed indirect evidence for this mechanism, demonstrating that BCG expressing the mannose-binding protein FimH had improved ability to adhere to urothelial cells and be internalized by them and also induced a more potent anti-tumor response as compared to wild type BCG. However, whether the improved efficacy of the FimH strain was through increased uptake by urothelial cells or via another mechanism was not shown [30].…”
Section: Interactions Between Bcg and Urothelial Cellsmentioning
confidence: 99%
“…BLCA is one of the most common and most aggressive malignancies, the worried is that little progress has been made in the treatment of BLCA in the last few decades ( Kimura et al, 2020 ; Lv et al, 2020 ). It is worth noticing that immunotherapy has shown great potential to treat MIBC and metastatic bladder cancer in the clinic ( Nair et al, 2020 ; Pfail et al, 2021 ; Zhang et al, 2022 ). Previous studies have found that macrophages exert different effects on immunotherapeutic responses in advanced cancers ( Petty and Yang, 2017 ; DeNardo and Ruffell, 2019 ; Zeng et al, 2020 ; Leblond et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These include lectin-drug conjugates and bacterial-based immunotherapies. The ConAepirubicin conjugate (Huo et al, 2022), and the adjuvant immunotherapies PA-MSHA (Wang et al, 2021) and rBCG-S.FimH (Zhang et al, 2022), were all shown to be more effective t h a n B C G , a g a i n s t b l a d d e r c a n c e r i n t h e mo u s e orthotropic model.…”
Section: Discussionmentioning
confidence: 99%
“…FimH is the distal component of type 1 fimbria that is expressed by many uropathogenic E. coli (UPEC) strains ( Emody et al., 2003 ; Gur et al., 2013 ), and plays a critical role in the interactions of UPEC with D-mannose -enriched bladder uroplakin Ia ( Zhou et al., 2001 ). Overexpression of FimH on the outer surface of a recombinant BCG (rBCG-S.FimH) was shown to markedly improve adhesion, expedite internalization into urothelial cells, and improve its immunotherapeutic effect for treating bladder cancer in mice, compared to the wild-type parental BCG ( Zhang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%